HOLOPROSENCEPHALY: CHROMOSOMAL ABNORMALITIES IN THE ETIOPATHOGENESIS OF 127 ANTENATAL CASES - Birsen Karaman; Selvi Ergin; Hülya Kayserili Karabey; Atıl Yüksel; Nihan Bilge Satkın; İbrahim Halil Kalelioğlu; Recep Has; Seher Başaran (İstanbul Tıp Fakültesi Dergisi)
Objective: Holoprosencephaly (HPE) is the most common developmental defect of midline cleavage in the human forebrain. Environmental, genetic, and multifactorial causes are involved in its etiology. About half of the cases have chromosome aberrations such as trisomies 13 and 18, triploidy and structural imbalances. Single gene mutations have been shown in ~25% of cases. In this retrospective study, we aimed to determine the etiological factors related to HPE in 127 fetuses. Material and Method: This study comprises 127 prenatally diagnosed fetal HPE samples from a period of 25 years, which were evaluated by karyotyping, fluorescence in situ hybridization (FISH) and aCGH investigation. Results: A total of 64 (50.39%) chromosome aberrations were identified in this cohort. The predominant chromosomal abnormality was trisomy 13 (n=38), which was followed by trisomy 18 (n=8) and triploidy (n=5). Terminal 7q deletion was the most frequent structural anomaly (n=10, of which 5 were de novo deletion, 4 were an unbalanced product of maternal translocations and one unknown in origin) and the deletion of 18p was detected in one case. In the remaining two cases, we detected trisomy 20 and pericentric inversion 11 coincidentally. Conclusion: This study, indicates that in the presence of clinical findings suggesting HPE, cytogenetic and molecular cytogenetic studies should be performed. An aCGH study must also be done for submicroscopic chromosomal anomalies, to determine their sizes, real breakpoints and identify possible novel genes that might play a role in HPE etiology.